Preferences of mobile fitness application on health related fitness component among varsity student / Muhamad Zaki Mohd Ramli - Mohd Ramli, Muhamad Zaki (Faculty of Sport Science and Recreation, 2018)
The aim of this study is to identify the preference of mobile fitness application on health related fitness component on varsity students. Three hundred and sixty seven (n=367) students have answered the online questionnaire that has been develop in this study. Pilot study was carried out in order to know the validity of the questionnaire. This study has used the preliminary study which is by making an observation on existing mobile application in order to know the key different on mobile application. Means rank analysis has been used in order to know the preference. The result shows that the most preferred component by varsity students is cardiovascular endurance, followed by muscular strength, muscular endurance, and flexibility and body composition. For the exercise selected, jogging has become the most preferred exercise on cardiovascular component, followed by the strength training for muscular strength. Preference in exercise for muscular endurance is body weight training (BWT) followed by Pilates method for flexibility and STEP exercise for body composition.